(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Poverty constitutes the underlying factor for poor health status among large masses in India. The era of globalization marked by unemployment, depleting wages, rising health care costs, hazardous working and living environment has clear gender specific impacts. The patriarchal forces act in alliance with the forces of globalization to accentuate gender related subordination. Hence, one needs to go beyond the biological determinants of health and understand that women’s poor health status is inextricably linked to their social and economic inequalities, which restrict their access to and control over resources. In doing so, we analyze and examine the factors which make women vulnerable to mortality, communicable diseases, mental health problems; occupational health hazards and impinges on their right to health and well-being. India accounts for the second highest maternal mortality rate in the world40. The figures are on a consistent rise, with National Family Health Survey (NFHS) II indicating an increase from 424 deaths per 100,000 live births in 1991 to 540 in 1997-98 and have remained stagnant till 200041. In numbers, this translates to one woman dying every five minutes primarily from sepsisinfection, haemorrhage, eclampsia, obstructed labour, abortion and anaemia. With 85% of pregnant women being anaemic, blood loss due to haemorrhage in pregnancy and labour can be fata A vicious circle of under nourishment and ill health is set in motion; poor nourished mothers give birth to low birth weight babies. Low birth weight babies have a greater risk of dying from diarrhoea and acute respiratory infections. Besides posing risks during pregnancy, anaemia increases women’s susceptibility to illnesses such as tuberculosis and malaria, and reduces the energy women require for daily activities.